Varicose veins of the small pelvis and pelvic congestion syndrome. A differentiated approach: the choice of method of contraception, treatment, prevention - Григоренко, А. Н.; Гордийчук, А. Б. (REPRODUCTIVE ENDOCRINOLOGY, 2017)
The article considers the main points that affect the quality of life of women with varicose veins of small pelvis with congestion and without it, in particular the use of hormonal methods of contraception, and also discussed the issues of diagnostics, prevention and treatment of these diseases. Algorithms of clinical tactics for conducting such patients are presented. Particular attention is focused on the features of the appointment of hormonal drugs in this category of women. You can determine the methods of treatment and avoid long-term unreasonable prescription of various medicine (especially hormones that will mask or worsen the course of the disease) if you select groups of women with varicose veins of the small pelvis without congestion and with it (reflux). Varicose veins of the small pelvis and pelvic congestion syndrome are conditions that require an interdisciplinary and differentiated approach. Symptoms of these conditions can be put on a mask of various gynecological, urological, traumatological diseases. Anatomical and physiological features of the structure of the veins and the regulation of their venous tone explain the possibility of forming a venous congestive syndrome in women. This can be due to two reasons: due to the violation of the outflow of venous blood or due to the obstruction of any vein of the ovary, any increase in intravascular pressure not controlled by the venous tone at the level of the pelvis. Varicose veins of the small pelvis and pelvic congestion syndrome remain unexplored until the end. There are no uniform standards for their diagnostics. Varicose veins of the small pelvis and pelvic congestion syndrome are different diseases which requiring an understanding of the mechanisms of their development and consequences. If a pelvic varicose veins are suspected, the first diagnostic test is usually ultrasound. Modern ultrasound technique can evaluate blood flow in various veins. To study the blood flow in the veins, laparoscopy, venography in combination with CT or MRI can also be performed.